Investigation of the factors influencing cavitation intensity during the ultrasonic treatment of molten aluminium - Tzanakis, I.; Lebon, G.S.B.; Eskin, D.G.; Pericleous, K. (Materials & design, 2016)
The application of ultrasound to casting processes is a subject of great interest: the resulting degassing, sonocrystallization, wetting, fragmentation, de-agglomeration and dispersion yield an improved cast material with fine grain structure. However, due to the lack of understanding of certain fundamentals involved in the process, the transfer and scale-up of this promising technology to industry has been hindered by difficulties in treating large volumes of liquid metal. Experimental results of ultrasonic processing of liquid aluminium with a 5-kW magnetostrictive transducer and a 20-mm niobium sonotrode producing 17-kHz ultrasonic waves are reported in this study. A high-temperature cavitometer sensor that is placed at different locations in the liquid melt, measured cavitation activity at various acoustic power levels and in different temperature ranges. The highest cavitation intensity in the liquid bulk is achieved below the surface of the sonotrode, at the lowest temperature, and when the applied power was 3.5kW. Understanding these ultrasonication mechanisms in liquid metals will result in a major breakthrough for the optimization of ultrasound applications in metal industries. [Display omitted] •Cavitation intensity in the melt is the most important process parameter.•Acoustic pressure measurements vs temperature were conducted for first time in Al.•Cavitation intensity in Al melt is mainly influenced by the distance from source.•Melt temperature and input power have similar impact on the cavitation intensity.